DESIGN AND FABRICATION OF 3D PRINTED MICROFLUIDIC PLATFORM - Lukito, Vincent
Microfluidics is the field and technological systems which allows fluid manipulation on a micro scale. Nowadays, several methods have been discovered to construct a microfluidic platform. However, most of these methods take time and require complex steps compared to using a 3D printer. Therefore, the focus of this research would be designing a 3D printed microfluidic platform and optimizing both the structural design and the application of soft lithography on 3D printed molds. Compared to other methods for 3D printing, this research would focus on stereolithography considering its high resolution and cost required. Therefore, in this paper, UV-related 3D printed parameters are optimized in order to optimally fabricate the designed 3D printed platforms and mold. Heating temperature and duration for soft lithography based fabrication will also be investigated in this paper. Computational Fluid Dynamics will assist mixing performance evaluation of several design combinations. Lastly, simple characterization tests will be attempted on 3D printed platforms. Through experiment, optimal printing parameters were found on connector module, chamber module, and 3D printed mold. The connector modules required 0.1 mm layer height, 8 bottom layer count, 15 s exposure time, 60 s bottom exposure time, 1 s light-off delay, and 0 s bottom light-off delay. It is found that soft lithography fabrication on 3D printed mold required baking at 75oC for an hour followed by further baking at 120oC at an hour. Simulation results showed that T+Spiral structural combinations yielded the best mixing performance. Lastly, 3D printed microfluidic platforms are hydrophillic with a friction factor of 72.65 for water at a velocity of 0.0631 x 10-3m/s. However, the dimensions of the fabricated platform in this study are still in the sub-millimeter range (400µm). Therefore, further optimization is required in order for the platform to become truly microfluidic.